Foreign workers' legal status in Indonesian - Parmika, Ahyar (2017)
Purpose - The employment of foreign workers in Indonesian workers market is merely set for particular positions and a certain period of time as clearly stipulated in Law Number 13 of 2013 on Labor and its implementation regulations. In practice, temporary employment agreement between the employer and the foreign workers habitually does not meet the applicable regulations. The agreements are often unwritten and not set in Indonesian language. Additionally, it has often exceeded the period of time set out in the Law. This is a real issue that has resulted in Legal problem, such as industrial disputes related to termination of employment concerning on employment status and compensation layoffs. Methodology - The research method used is normative juridical research and supported by empirical juridical, it is necessary to approach the existing problems. The approach used in this type of research is the legislative approach, as well as the case approach. Findings - An employment agreement specified time for foreign workers are made not in written form and not in the Indonesian language remain valid and are binding for employers and foreign workers, because in principle the employment agreement specified time has met the terms of the validity of a workers agreement. As regulated in Article 52 paragraph (1) of Law no. 13 of 2003 certain time employment agreement is not made in accordance with the provisions of Article 57 paragraph (1) of Law No. 13 of 2003 resulted considers employment agreement specified time into employment agreements specified time with all the legal consequences, but especially for employment agreement specified time for foreign workers apply lex different labor agreement specific time for workers in the country so that the agreement certain time employment does not necessarily considered a certain time employment agreement. Lex specialis is due historically and the purpose of the formation of articles on foreign workers in Law No.13 of 2003 which is different from domestic workforce..